2020
DOI: 10.1093/pcp/pcaa063
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Composition and Associated Gene Expression Patterns during Pollen Germination and Pollen Tube Growth in Olive (Olea europaea L.)

Abstract: Pollen lipids are essential for sexual reproduction but our current knowledge regarding lipid dynamics in growing pollen tubes is still very scarce. Here, we report unique lipid composition and associated gene expression patterns during olive pollen germination. Up to 376 genes involved in the biosynthesis of all lipid classes, except suberin, cutin and lipopolysaccharides, are expressed in the olive pollen. The fatty acid profile of the olive pollen is markedly different compared with other plant organs. Tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 127 publications
2
30
0
Order By: Relevance
“…In summary, all these results suggest that the relative contribution of PDAT and DGAT enzymes to TAG synthesis in olive seems to be tissue-dependent. Supporting this hypothesis, previous studies from our group indicated that PDAT activity may also participate in the TAG biosynthesis in olive callus culture (Hernández et al, 2008), while during pollen germination and pollen tube growth the contribution of DGAT1 but not DGAT2, PDAT1-1 and PDAT1-2 to de novo TAG synthesis has been reported (Hernández et al, 2020a).…”
Section: Developmental Expression Of Phospholipid:diacylglycerol Acyltransferase Genes In the Olive Fruit In Relation To The Oil Contentsupporting
confidence: 60%
See 1 more Smart Citation
“…In summary, all these results suggest that the relative contribution of PDAT and DGAT enzymes to TAG synthesis in olive seems to be tissue-dependent. Supporting this hypothesis, previous studies from our group indicated that PDAT activity may also participate in the TAG biosynthesis in olive callus culture (Hernández et al, 2008), while during pollen germination and pollen tube growth the contribution of DGAT1 but not DGAT2, PDAT1-1 and PDAT1-2 to de novo TAG synthesis has been reported (Hernández et al, 2020a).…”
Section: Developmental Expression Of Phospholipid:diacylglycerol Acyltransferase Genes In the Olive Fruit In Relation To The Oil Contentsupporting
confidence: 60%
“…In olive, two DGAT genes ( OeDGAT1 and OeDGAT2 ) have been isolated and characterized, which show overlapping but distinct expression patterns during olive mesocarp growth ( Giannoulia et al, 2000 ; Banilas et al, 2011 ). In contrast, no PDAT genes have been characterized in olive to date, although two genes ( OePDAT1-1 and OePDAT1-2 ) have been identified in the olive pollen ( Hernández et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Neutral lipids including TAG in tobacco pollen were reduced during 6 h of pollen germination, similar to lipid bodies in olive pollen after 7 h of pollen germination ( Rodriguez-Garcia et al, 2003 ). Another study detailed changes in neutral and polar lipid fractions over olive pollen germination ( Hernández et al, 2020 ). Interestingly, they found the fatty acid composition from total lipids was significantly altered, although the TAG content remained unchanged during the first 6 h of germination ( Hernández et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study detailed changes in neutral and polar lipid fractions over olive pollen germination ( Hernández et al, 2020 ). Interestingly, they found the fatty acid composition from total lipids was significantly altered, although the TAG content remained unchanged during the first 6 h of germination ( Hernández et al, 2020 ). These results indicate lipid dynamic changes are stage- and species-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, ω-3 fatty acid desaturases have been proven to use C18:2 as substrates to produce 18:3 in the plastid, where FAD7 and FAD8 are located, and in the ER where FAD3 are found [5]. In plants, the accumulation of 18:3 under the activity of ω-3 fatty acid desaturases, particularly FAD3 has been demonstrated in several studies, such as in soybean [108,109], in rice [110], in olive [111][112][113], in peanut [114], in flax [115], in walnuts [116], in cowpea [117], in alfalfa [118], in peach aphid [119] and now in C. sativa, according to the current study.…”
Section: 4mentioning
confidence: 99%